BIOFERTILISASI BAKTERI Rhizobium PADA TANAMAN KEDELAI (Glycine Max (L) Merr.) - Tini Surtiningsih; Farida; Tri Nurhariyati (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2009)
The aim of this research want to know the influence of the addition Rhizobium bacteria species, dose and combination both of them, on growth and production of soybean plant (Glycine max (L) Merr.). The experimental design of this research was factorial design 4×2, 4 species of Rhizobium are R1 = Rhizobium japonicum, R2 = R. phaseoli, R3 = R. leguminosarum, R4 = mixture of R1, R2 and R3, and 2 dose of inoculan Rhizobium (D1 = 5 m/plant, and D2 = 10 ml/plant) with 1010 sel bacteria/ml and 5 replications. Independent variable is species of Rhizobium, dose of inoculan Rhizobium and combination both of them. Dependent variable is dry matter, weight of nodules and dry weight of seeds. The harvest data was analyzed by Kruskal-Wallis Test using 5% level (a = 0.05) followed by Mann- Whitney Test. The result of this research show that species of Rhizobium, dose of inoculan Rhizobium and combination both of them present insignificant result (a > 0.05) on soybean growth and production, but the mixture of Rhizobium species with high level dose of bacteria, present better result than single species with low dose of bacteria.